Comparison of clinical outcomes and risk factors for COVID-19 infection in cancer patients without anticancer treatment and noncancer patients - Yang, Sen; Zhao, Huaxin; Cui, Ran; Ma, Le; Ge, Xuhua; Fu, Qiangqiang; Yu, Dehua; Niu, Xiaomin (Frontiers in Public Health, 2022)
Background: Previous studies have shown that cancer patients have higher rates of coronavirus disease 2019 (COVID-19) infection and mortality than noncancer patients. However, the differences between cancer patients undergoing regular follow-up without anticancer treatment and noncancer patients with COVID-19 have remained insufficiently investigated. Methods: A retrospective case‒control study of fifty-two patients with COVID-19 infection was performed with a 1:3 matched proportion of cancer patients undergoing regular follow-up without anticancer treatment and noncancer patients. The demographic characteristics, clinical data, laboratory tests, treatment, and complications of patients were collected from medical records. Chi-square tests and univariate and multivariate regressions were performed to assess the differences between these two cohorts of COVID-19 patients with and without cancer and risk factors for severe events in COVID-19 patients. Results: Increased C-reactive protein (CRP) (>4 mg/L) (p=0.015) and lactate dehydrogenase (LDH) (>243 IU/L) (p=0.038) were identified as risk factors for severe events in all enrolled COVID-19 patients based on multivariate analysis, but cancer as a chronic disease (p=1.000) was not identified as an independent risk factor for severe events in COVID-19 patients. Compared with noncancer patients, cancer patients had a significantly longer median hospitalization time (29 days vs. 19 days, p=0.048) and a higher incidence of hypoalbuminemia complications (84.6% vs. 46.2%, p=0.016). Conclusions: Increased CRP and LDH were risk factors for severe events in all enrolled COVID-19 patients, and an increased incidence of hypoalbuminemia complications and longer hospitalization were noted in COVID-19 cancer patients undergoing regular follow-up without anticancer treatment compared with noncancer patients.